Implementasi Metode Montessori Dalam Menumbuhkan Kemandirian Anak Melalui Daily Life Skills Di TK Raudhatul Jannah - Danisya Alzura; Herman Herman; Angri Lismayani (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Undergraduate Thesis. The Implementation of the Montessori Method in Fostering Children's Independence through Daily Life Skills at TK Raudhatul Jannah. Early Childhood Teacher Education Program, Faculty of Education, Universitas Negeri Makassar. Supervised by Herman and Angri Lismayani.This study aims to describe the implementation of the Montessori method in fostering children's independence through daily life skills activities in Group B1 at TK Raudhatul Jannah. The research employed a descriptive qualitative approach, with the principal, classroom teacher, and students as data sources. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the implementation of the Montessori method was carried out through the provision of a prepared environment, guided freedom in choosing activities, and daily life skill activities such as organizing learning materials, wearing shoes, pouring water, and maintaining classroom order. These activities contributed to the development of children’s independence in physical, social, and emotional aspects, as reflected in their ability to perform basic tasks independently, as well as increased self-confidence and responsibility